The South African REIPPP Two-tier CSP Tariff: Implications for a Proposed Hybrid CSP Peaking System. (May 2015) - Silinga, C.; Gauché, P.; Rudman, J.; Cebecauer, T.
Abstract: We proposed a case for a short term CSP peaking system of plants for South Africa in a previous study. A virtual hybrid system including planned Open Cycle Gas Turbines and a spatial-size optimized fleet of CSP plants suggests a number of benefits. A progressive rollout exceeding 3, 000 MW of CSP in 15 years: mitigates cost of capital; incrementally reduces fuel dependency; leads to a local CSP learning rate; adds reserve margin; and leads to a lower system LCOE. In this paper, we study the effect that the two tier tariff introduced in the Independent Power Producer programme of the Department of Energy has on a 3, 300 MW capacity of CSP plants that is proposed as a peaking CSP system. We use the same spatial-temporal analysis approach as conducted in the earlier study. Two scenarios are developed and presented in this study in order to determine the implications of the two-tier tariff structure. The profitability – Levelized Profit of Energy of the CSP system is used as criteria for validation.Scenario 1 is based on the previous peaking CSP study load profile. It shows that the two-tier tariff structure generates 29 % less revenue than the fixed tariff.Scenario 2 is based on the re-optimized energy delivery from CSP system. This scenario shows that re-optimized energy delivery approach of CSP systemmakes the CSP system more profitable under the two-tier tariff structure.